Crops and Cropping Systems in Dinajpur Region (Bangladesh Rice Journal, 2018)
The development of agricultural planning largely depends on the reliable and comprehensive statistics of the existing cropping patterns, cropping intensity and crop diversity of a particular area, which will provide a guideline to the policy makers, researchers, extensionists and development workers. A study was undertaken over all the upazilas of Dinajpur region during 2016 using pre-tested semi-structured questionnaire with a view to document of the existing cropping patterns, intensity and diversity for the region. The most important cropping pattern Boro-Fallow-T. Aman occupied about 41% of net cropped area (NCA) of the region with its distribution over all the upazilas. The second largest area, 9% of NCA, was covered by Wheat-Fallow-T. Aman, which was spread over 18 upazilas. A total of 112 cropping patterns were identified in the whole region. The highest number of cropping patterns was identified 30 in Boda upazila of Panchagarh district while the lowest was 11 in Kaharol upazila of Dinajpur district. The lowest crop diversity index (CDI) was reported 0.708 in Birampur followed by 0.753 in Ghoraghat of Dinajpur. The highest CDI was reported 0.955 in Ranisonkail followed by 0.952 in Baliadangi of Thakurgaon. The range of cropping intensity was recorded 206-249% whereas the maximum value was found for Khansama of Dinajpur and minimum for Boda of Panchagarh district. As a whole, CDI and cropping intensity for Dinajpur region were calculated 0.924 and 229% respectively, which indicates that the land use and crop diversification is not quite enough for the national demand.Bangladesh Rice j. 2017, 21(2): 143-156